Gothic Things : Dark Enchantment and Anthropocene Anxiety - Weinstock, Jeffrey Andrew (Book collections on Project MUSE., 2023)
"Offering an innovative approach to the Gothic, Gothic things: dark enchantment and anthropocene anxiety breaks ground with a new materialist analysis of the genre, highlighting the ways that, since its origins in the eighteenth century, the Gothic has been intensely focused on "ominious matter" and "thing power." In chapters attending to gothic bodies, spaces, books, and other objects, Gothic Things argues that the Gothic has always been about what happens when objects assume mysterious animacy or poetency and when human beings are reduced to the status of just one thing among many--more powerful--others. In exploring how the Gothic insistently decenters the human, Jeffrey Andrew Weinstock reveals human beings to be enmeshed in networks of human and nonhuman forces mostly outside of their control. Gothic Things thus resituates the Gothic as the uncanny doppelganger of twenty-first-century critical and cultural theory, lurking just beneath the surface (and sometimes explicitly surfacing) as it haunts considerations of how human beings interact with objects and their environment. In these pages the Gothic offers a dark reflection of the contemporary "nonhuman turn," expressing a twenty-first-century structure of feeling undergirded by anxiety of the fate of the human: spectrality, monstrosity, and apocalypse. Substituting horror for hope, the Gothic, Weinstock explains has been a philosophical meditations to live more harmoniously with the world around us."--